Design of a low power 60GHz OOK receiver in 65nm CMOS technology - Lu, Zhenghao (2013)
This paper presents the design of a low-power millimeter wave receiver for Gbps short range wireless communications in the 60GHz frequency range. The scope of this paper covers the system design of the OOK direct conversion receiver, the design of a novel 60GHz low-noise amplifier, the co-design of the mixer with the IF amplifier and the design of a IF variable gain amplifier. The full receiver is realized in Global Foundry 65nm CMOS technology. The extracted simulation results show that the receiver is able to work from 50GHz-70GHz with a data rate higher than 1Gbps while consuming a current of about 25mA from a standard 1.2V supply voltage at maximum gain.